Generic variation across legislative writing. A contrastive analysis of the UNCITRAL Model Law and Brazil's Arbitration Law - Frade, Celina (HERMES - Journal of Language and Communication in Business, 2004)
The nature of legislation is to control human relations and actions by words. Legislative writing displays relative uniformity though, as a genre, some variations are allowed across legal systems, as in the case of arbitration laws. This article focuses on the generic variation of two arbitration laws: the UNCITRAL Model Law on the International Commercial Arbitration (hereafter UNCITRAL) and the Brazilian Arbitration Law 9.307/1996 (hereafter BAL). Arbitration is an alternative form of conﬂ ict resolution based upon the free will of the parties to invest arbitrators, (not the judiciary) with the jurisdiction to settle disputes in a contract of commercial nature. The claim is that the analysis (at surface level) of textual organization and legislative style in the data cannot account alone for an explanation of how legislative information is functionally realized in order to achieve its communicative intent. To explain this we, therefore, also consider how legislative information is packaged by means of some textualization devices (qualiﬁ cational insertions, binomial and multinomial structures and textual-mapping) and conclude by showing how recontextualization is realized in the data by means of generality, fuzziness and vagueness of terms and expressions.